Perspectives of Post-Acute Transition of Care for Cardiac Surgery Patients - Stoicea, Nicoleta; You, Tian; Eiterman, Andrew; Hartwell, Clifton; Davila, Victor; Marjoribanks, Stephen; Florescu, Cristina; Bergese, Sergio Daniel; Rogers, Barbara (Frontiers in Cardiovascular Medicine, 2017)
Post-acute care (PAC) facilities improve patient recovery, as measured by activities of daily living, rehabilitation, hospital readmission, and survival rates. Seamless transitions between discharge and PAC settings continue to be challenges that hamper patient outcomes, specifically problems with effective communication and coordination between hospitals and PAC facilities at patient discharge, patient adherence and access to cardiac rehabilitation (CR) services, caregiver burden, and the financial impact of care. The objective of this review is to examine existing models of cardiac transitional care, identify major challenges and social factors that affect PAC, and analyze the impact of current transitional care efforts and strategies implemented to improve health outcomes in this patient population. We intend to discuss successful methods to address the following aspects: hospital-PAC linkages, improved discharge planning, caregiver burden, and CR access and utilization through patient-centered programs. Regular home visits by healthcare providers result in decreased hospital readmission rates for patients utilizing home health care while improved hospital-PAC linkages reduced hospital readmissions by 25%. We conclude that widespread adoption of improvements in transitional care will play a key role in patient recovery and decrease hospital readmission, morbidity, and mortality.